Escala diagramática e influência de sistemas de produção na ocorrência do crestamento gomoso da melancia - Sousa, Samilla Candida Rodrigues (2013)
CHAPTER 1 - The gummy stem blight, caused by the fungus D. bryoniae, is a disease commonly found in watermelon cultivated in several countries. In Brazil, there are numerous studies related to the disease, but there are not uniform methods for quantifying of disease severity in the field. Thus, we developed a diagrammatic scale based on scanned photos of watermelon leaves infected with D. bryoniae. The scale developed showed levels of 0; 10; 20; 45; 65 and 90% of severity. The scale validation was divided into two parts: initially, 10 evaluators (half with experienced and other half without experience) estimated the disease severity based on the initial observation of 100 photos of watermelon leaves with symptoms of the disease at different severity levels. Before, the same evaluators estimated the disease severity with the support of the scale prepared from the Quant program. Data were analyzed using linear regression and were obtained angular, linear, and correlation coefficients. Based on these data, we determined the accuracy and precision of the evaluations. The correlation coefficients (R2) ranged from 0.88 - 0.97 for the experienced evaluators and from 0.55 - 0.95 for the inexperienced evaluators. The average angular coefficient (A) for inexperienced evaluators was 20.42 and 8.61 with and without the support of diagrammatic scale, respectively. Experienced evaluators showed values of average linear coefficient of 5.30 and 1.68 with and without the support of diagrammatic scale, respectively. The absolute errors analysis indicated that the use of diagrammatic scale contributed to minimize the flaws in the severity levels estimation. The diagrammatic scale proposed shown adequate for gummy stem blight severity evaluation in watermelon. CHAPTER 2 - The gummy stem blight (Didymella bryoniae) is a disease that affects the productivity of watermelon leading to losses over 40%. This study aimed to evaluate the efficiency of different production systems in control of gummy stem blight in watermelon for to establish efficient methods to combat the disease. There were applied the following treatments: conventional tillage (T1), integrated management (T2) and organic management (T3). In T1 and T2 were applied mineral fertilization and T3 was used bovine manure. There was application of fungicides and insecticides in commercial dose in T1 and T2, being after soil chemical analysis in T2. Disease severity was assessed by grading scale. The experimental design was randomized blocks. The severity of gummy stem blight has increased substantially during the fruit formation. Watermelon plants grown with integrated management (T2) showed lower levels of disease severity, while plants in organic management (T3) exhibited higher levels of severity. We conclude that management based on judicious accompaniments in field represents best way to achieve the phytosanitary aspect adequate for cultivation of watermelon in Tocantins.